Account of eco‐friendly energy conversion reaction: Iron‐based nitrogen electrofixation - Liyuan Xu; Zheng Zhu; Jingjing Duan; Sheng Chen (Electron)
Abstract Ammonia is a crucial raw ingredient used in the manufacturing of fertilizers and pharmaceuticals, which are major sectors of the national economy in the chemical and agricultural industries. The conventional Haber–Bosch method is still in use in the industry today to manufacture NH3, and the production process emits a significant quantity of CO2, which does not match the current standards for the achievement of carbon neutrality. The nitrogen reduction reaction (NRR) technology has garnered a lot of attention lately because of its benefits, which include being environmentally friendly, sustainable, and able to function in mild environments. However, NRR is still in its early stages of development and confronts numerous difficult issues, including slow reaction kinetics, low ammonia yield rates and Faradaic efficiency (FE), and a dearth of effective research on nitrogen fixation as a whole. This paper aims to promote the industrialization of NRR, summarizing the progress of iron‐based catalysts, including single atomic catalysts, organic frameworks, metal oxides the, and alloys. Eventually, this paper discusses the strategies for improving NH3 yield rates and FE, improving reaction kinetics, and building a sustainable overall nitrogen fixation system. The development of iron‐based catalysts in other fields has also been prospected.